1991
DOI: 10.1159/000204892
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Phagocytic Activity in Sickle Cell Disease

Abstract: The phagocytic activity of peripheral blood monocytes from sickle cell disease patients and normal controls was studied using a monocyte monolayer assay. Phagocytosis of antibody-coated red cells by monocytes from patients in stable condition and in normal controls did not differ significantly (7.1 ± 1.5 vs. 5.3 ± 0.9%). However, monocytes from sickle cell disease patients during vasoocclusive crises demonstrated increased phagocytic activity compared to the normal controls (11.0 ± 2.7 vs. 5.3 ± 0.9%, p < 0.02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Another would be that the synthetic capacity for TNF‐α in the monocytes from these patients is inherently diminished. However, previous studies by other investigators have predominantly shown that monocytes from patients with SCD function normally (Vilela et al ., 1990; Mendoza et al ., 1991) or had minimally reduced phagocytic activity (Vilela et al ., 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another would be that the synthetic capacity for TNF‐α in the monocytes from these patients is inherently diminished. However, previous studies by other investigators have predominantly shown that monocytes from patients with SCD function normally (Vilela et al ., 1990; Mendoza et al ., 1991) or had minimally reduced phagocytic activity (Vilela et al ., 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Open circles represent data outside the 10th and 90th percentiles. Mendoza et al, 1991) or had minimally reduced phagocytic activity (Vilela et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…For example, phagocytic activity rises during VOCs 56. Neutrophil chemotaxis is normal or clearly reduced in the steady state of the disease but increases during VOC crises57.…”
Section: Etiology Of Risks Of Infections In Thalassemia and Hemoglobimentioning
confidence: 99%
“…The monocyte monolayer assay (MMA) has been used for more than 35 years to predict the hemolytic significance of a red blood cell (RBC) auto‐ or alloantibody . In recent years, this assay has been adapted to examine intravenous immunoglobulins (IVIG) implicated in postadministration hemolysis .…”
mentioning
confidence: 99%